D-Day girls : the spies who armed the resistance, sabotaged the Nazis, and helped win World War II - Rose, Sarah. 1974- (Crown, 2019)
"The dramatic, inspiring story of the extraordinary women recruited by Britain's elite spy agency to sabotage the Nazis, shore up the Resistance, and pave the way for Allied victory in World War II."--Provided by publisher.